A new robust control strategy for axial flux permanent magnet motor applied on legged lunar robots. (February 2023) - Chen, Zheng-Han; Xu, Zhao-Dong; Lu, Hong-Fang; Yang, Jian-Zhong; Yu, Deng-Yun; Zhu, Chen; Zhen, Sheng-Chao; Zheng, Hong-Mei
Legged robots have the advantage of strong terrain adaptability in lunar exploration. A new robust controller is designed for axial flux permanent magnet motors applied on the legged lunar robots to diminish the disturbance from uncertainty and external circumstance. The theoretical verification is carried out through Lyapunov stability theory. The numerical simulation and real-time experiment are carried out to access the stability and dynamic property of the systems adopting the proposed controller. The results are compared with the traditional control strategies to demonstrate the advantages of the proposed controller. The new robust controller contributes to the dynamic stability of legged lunar robots and is also appropriate for the similar mechanical systems.